Influence of the chosen handwriting style on reading and writing skills of second graders - Pearson, María Rufina; Londra, Franco; Pearson, Josefina (Anales de Psicología / Annals of Psychology, 2026)
Currently, the literature is inconclusive regarding the role of typography in reading and writing performance of primary school students. This study aimed to investigate the impact of the typography used by students (uppercase, script, cursive) on spelling, use of punctuation and capital letters, richness of composition, and writing-reading fluency. A total of 152 second-grade students from middle socioeconomic level schools in Buenos Aires, Argentina, participated. The students completed tasks involving the dictation of words and pseudowords, writing, writing fluency, graphomotor skills and reading fluency. Results showed that students who used script typography wrote a greater number of correct words and sentences, made fewer spelling errors, wrote more letters per minute, and read with greater fluency compared to those who used uppercase or cursive, all with p < .045. Accuracy in pseudowords and phonological errors were explained by graphomotor development, both with p < .007. The results provide evidence to the debate on which typography to use and are discussed based on its application to the school environment.